2014
DOI: 10.1016/j.pharmthera.2013.10.011
|View full text |Cite|
|
Sign up to set email alerts
|

The biology of Nociceptin/Orphanin FQ (N/OFQ) related to obesity, stress, anxiety, mood, and drug dependence

Abstract: Nociceptin/Orphanin FQ (N/OFQ) is a 17 amino acid peptide that was deorphanized in 1995. The generation of specific agonists, antagonists and receptor deficient mice and rats has enabled progress in elucidating the biological functions of nociceptin. In addition, radio-imaging technologies have been advanced for investigation of this system in animals and humans. Together with traditional neurobehavioral techniques, these tools have been utilized to identify the biological significance of the N/OFQ system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(184 citation statements)
references
References 195 publications
(234 reference statements)
10
168
0
6
Order By: Relevance
“…In a separate study it was demonstrated that Ro 64-6198 is also active in reducing ethanol self-administration and preventing relapse of ethanol drinking (Kuzmin et al, 2007). These results obtained with Ro 64-6198 are in line with a rather large number of findings obtained with N/OFQ, or other NOP ligands, suggesting that NOP agonists are worthy of further exploration as innovative treatments for drug abuse (Zaveri, 2011;Witkin et al, 2014). However, one should keep in mind the observation that NOP receptor agonists appear to be more efficacious for attenuation of CPP than self-administration, as discussed above, once again displaying the complicated nature of the NOP receptor system.…”
Section: B Nociceptin/orphanin Fq Unrelated Peptidessupporting
confidence: 57%
“…In a separate study it was demonstrated that Ro 64-6198 is also active in reducing ethanol self-administration and preventing relapse of ethanol drinking (Kuzmin et al, 2007). These results obtained with Ro 64-6198 are in line with a rather large number of findings obtained with N/OFQ, or other NOP ligands, suggesting that NOP agonists are worthy of further exploration as innovative treatments for drug abuse (Zaveri, 2011;Witkin et al, 2014). However, one should keep in mind the observation that NOP receptor agonists appear to be more efficacious for attenuation of CPP than self-administration, as discussed above, once again displaying the complicated nature of the NOP receptor system.…”
Section: B Nociceptin/orphanin Fq Unrelated Peptidessupporting
confidence: 57%
“…Consistent with this localization, evidence suggests that the N/OFQ system is involved in the regulation of several addiction-related phenomena, including drug intake, withdrawal, and relapse for a variety of psychotropic agents including opioids, psychostimulants, and ethanol (Ciccocioppo et al, 2000a;Kallupi et al, 2014;Witkin et al, 2014;Zaveri, 2011).…”
Section: Introductionmentioning
confidence: 73%
“…The effects of N/OFQ on feeding are well documented (for review, see Witkin et al, 2014). Hyperphagia is consistently observed after intracerebroventricular administration of N/OFQ into either the lateral or third ventricle but not the fourth ventricle (Pomonis et al, 1996;Polidori et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NOP is expressed in the peripheral nervous system as well as in the gastrointestinal tract, smooth muscles, and in cells of the immune system. Initially, N/OFQ was found to produce hyperalgesia, leading to the naming the peptide nociceptin (Meunier et al, 1995); however, in addition to pain, N/OFQ modulates other CNS behaviors, including stress and anxiety, depression, substance abuse, prolactin secretion, locomotor activity, body temperature, memory, and feeding (Mustazza and Bastanzio, 2011;Gavioli and Calo', 2013;Singh et al, 2013;Witkin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%